The in vitro pharmacology of ZM 241385, a potent, non-xanthine A2a selective adenosine receptor antagonist. - Poucher, S. M. (1995)
1. This paper describes the in vitro pharmacology of ZM 241385 (4-(2-[7-amino-2-(2-furyl) [1,2,4]-triazolo[2,3-a][1,3,5]triazin- 5-yl amino]ethyl) phenol), a novel non-xanthine adenosine receptor antagonist with selectivity for the A2a receptor subtype. 2. ZM 241385 had high affinity for A2a receptors. In rat phaeochromocytoma cell membranes, ZM 241385 displaced binding of tritiated 5'-N-ethylcarboxamidoadenosine (NECA) with a pIC50 of 9.52, (95% confidence limits, c.l., 9.02-10.02). In guinea-pig isolated Langendorff hearts, ZM 241385 antagonized vasodilatation of the coronary bed produced by 2-chloroadenosine (2-CADO) and 2-[p-(2-carboxyethyl) phenethylamino]-5'-N-ethylcarboxamidoadenosine (CGS21680) with pA2 values of 8.57 (c.l., 8.45-8.68) and 9.02 (c.l., 8.79-9.24) respectively. 3. ZM 241385 had low potency at A2b receptors and antagonized the relaxant effects of adenosine in the guinea-pig aorta with a pA2 of 7.06, (c.l., 6.92-7.19). 4. ZM 241385 had a low affinity at A1 receptors. In rat cerebral cortex membranes it displaced tritiated R-phenylisopropyladenosine (R-PIA) with a pIC50 of 5.69 (c.l., 5.57-5.81). ZM 241385 antagonized the bradycardic action of 2-CADO in guinea-pig atria with a pA2 of 5.95 (c.l., 5.72-6.18). 5. ZM 241385 had low affinity for A3 receptors. At cloned rat A3 receptors expressed in chinese hamster ovary cells, it displaced iodinated aminobenzyl-5'-N-methylcarboxamido adenosine (AB-MECA) with a pIC50 of 3.82 (c.l., 3.67-4.06). 6. ZM 241385 had no significant additional pharmacological effects on the isolated tissues used in these studies at concentrations three orders of magnitude greater than those which block A2a receptors.(ABSTRACT TRUNCATED AT 250 WORDS)